(untitled) (Journal of Nepal Geological Society, 2018)
Sanshandao Gold Mine is the first and largest mine operating below sea level in China. Mining has been practiced in this region for at least 25 years. In recent years, buildings above the mining area have been extensively damaged. GPS (with 315 monitoring points) was used to monitor the ground deformation since 2009. Ground deformation induced by mining is much more complex in metal mine than that in coal mines due to the well-developed joints, high tectonic stress and several intersecting faults. All of the factors are analyzed in this study. The results show that discontinuous deformation has occurred on the surface because of the sliding to F3 (name of fault), and there are two motion patterns of F3 during the mining process. Additionally, joints in rock masses with steep dip angles contribute to the vertical displacement and joints with shallow dip angles contribute to the horizontal displacement. Meanwhile, high tectonic stress dramatically enlarges the scale of ground deformation, especially with respect to the horizontal displacement. This deformation results in a striped formation of compressed and stretched regions. Additionally, high-risk and potential risk areas are identified in this study. Finally, the successive data measured since 2009 can contribute to a deeper understanding of ground deformation in metal mine.